Advanced power electronics converters : PWM converters processing ACvoltages - Santos Jr., Euzeli Cipriano dos; Silva, Edison Roberto Cabral da, 1942- (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
'This book covers power electronics, in depth, by presenting the basic principles and application details, which can be used both as a textbook and reference book. Introduces a new method to present power electronics converters called Power Blocks Geometry (PBG) Applicable for courses focusing on power electronics, power electronics converters, and advanced power converters Offers a comprehensive set of simulation results to help understand the circuits presented throughout the book'--
'This book focuses on the PWM power converters operating in conjunction with the AC utility'--
Machine generated contents note: Advanced Power Electronics Converters PWM Converters Processing AC Voltages Summary 1. Chapter 1. Introduction 1.1 Introduction 1.2 Background 1.3 History of Power Switches and Power Converters 1.4 Applications of Power Electronics Converters 1.5 Summary 1.6 References 2. Chapter 2. Power Switches and Overview of Basic Power Converters 2.1 Introduction 2.2 Power Electronics Devices as Ideal Switches 2.2.1 Static Characteristics 2.2.2 Dynamic Characteristics 2.3 Main Real Power Semiconductors Devices 2.3.1. Spontaneous Conduction/Spontaneous Blocking 2.3.2. Controlled Conduction/Spontaneous Blocking Devices 2.3.3. Controlled Conduction/Controlled Blocking Devices 2.3.4. Spontaneous Conduction/Controlled Blocking Devices 2.4 Basic converters 2.4.1. Dc-dc Conversion 2.4.2. Dc-ac Conversion 2.4.3. Ac-dc Conversion 2.4.4. Ac-ac Conversion 2.5 Summary 2.6 References 3. Chapter 3. Power Electronics Converters Processing AC Voltage and Power Blocks Geometry 3.1 Introduction 3.2 Principles of Power Blocks Geometry (PBG) 3.3 Description of Power Blocks 3.4 Application of PBG in Multilevel Configurations 3.4.1. Neutral-Point-Clamped Configuration 3.4.2. Cascade Configuration 3.4.3. Flying Capacitor Configuration 3.4.4. Other Multilevel Configurations 3.5 Application of PBG in ac-dc-ac Configurations 3.5.1. Three-phase to three-phase configurations 3.5.2. Single-phase to single-phase configurations 3.6 Summary 3.7 References 4. Chapter 4. Neutral-Point-Clamped Configuration 4.1 Introduction 4.2 Three-level configuration 4.3 PWM Implementation (Half-Bridge Topology) 4.4 Full-bridge Topologies 4.5 Three-phase NPC Converter 4.6 Non-Conventional Arrangements by Using Three-Level Legs 4.7 Unbalanced Capacitor Voltage 4.8 Four-level Configuration 4.9 PWM Implementation (Four-level Configuration) 4.10 Full-bridge and Other Circuits (Four-level Configuration) 4.11 Five-level Configuration 4.12 Summary 4.13 References 5. Chapter 5. Cascade Configuration 5.1 Introduction 5.2 Single H-bridge Converter 5.3 PWM Implementation of a Single H-bridge Converter 5.4 Three-phase converter - one H-bridge converter per phase 5.5 Two H-bridge Converters 5.6 PWM Implementation of Two Cascade H-bridges 5.7 Three-phase converter - two Cascade H-bridges per phase 5.8 Two H-bridge Converters (Seven- and Nine-level topologies) 5.9 Three H-bridge Converters 5.10 Four H-bridge Converters and Generalization 5.11 Summary 5.12 References 6. Chapter 6. Flying-Capacitor Configuration 6.1 Introduction 6.2 Three-level configuration 6.3 PWM Implementation (Half-Bridge Topology) 6.4 Flying Capacitor Voltage Control 6.5 Full-bridge Topology 6.6 Three-phase FC Converter 6.7 Non-Conventional FC Converters with Three-level Legs 6.8 Four-level Configuration 6.9 Generalization 6.10 Summary 6.11 References 7. Chapter 7. Other Multilevel Configurations 7.1 Introduction 7.2 Nested configuration 7.3 Topology with Magnetic Element at the Output 7.4 Active-Neutral-Point-Clamped Converters 7.5 More Multilevel Converters 7.6 Summary 7.7 References 8. Chapter 8. Optimized PWM Approach 8.1 Introduction 8.2 Two-leg Converter 8.2.1. Model 8.2.2. PWM Implementation 8.2.3. Analog and Digital Implementation 8.2.4. Influence of [mu] for PWM implementation 8.3 Three-leg Converter and Three-phase Load 8.3.1. Model 8.3.2. PWM Implementation 8.3.3. Analog and Digital Implementation 8.3.4. Influence of [mu] for PWM implementation in a three-leg converter 8.3.5. Influence of the Three-Phase Machine Connection over Inverter Variables 8.4 Space Vector Modulation (SVPWM) 8.5 Other Configurations with CPWM 8.5.1. Three-leg Converter - Two-phase machine 8.5.2. Four-leg Converter 8.6 Non-Conventional Topologies with CPWM 8.6.1. Inverter with Split-Wound Coupled Inductors 8.6.2. Z-Source Converter 8.6.3. Open-end Winding Motor Drive System 8.7 Summary 8.8 References 9. Chapter 9. Control Strategies for Power Converters 9.1 Introduction 9.2 Basic Control Principles 9.3 Hysteresis control 9.3.1 Application of the hysteresis control for dc motor drive 9.3.2 Hysteresis control for regulating an ac variable 9.4 Linear control - dc variable 9.4.1 Proportional controller: RL load 9.4.2 Proportional controller: dc motor drive system 9.4.3 Proportional-Integral controller: RL load 9.4.4 Proportional-Integral controller: Dc motor 9.4.5 Proportional-Integral-Derivative controller: dc motor 9.5 Linear control - ac variable 9.6 Cascade control strategies 9.6.1 Rectifier circuit: voltage-current control 9.6.2 Motor drive: speed-current control 9.7 Summary 9.8 References 10. Chapter 10. Single-phase to Single-phase Back-to-Back Converter 10.1 Introduction 10.2 Full-Bridge Converter 10.2.1. Model 10.2.2. PWM Strategy 10.2.3. Control Approach 10.2.4. Power Analysis 10.2.5. Dc-link Capacitor Voltage 10.2.6. Capacitor Bank Design 10.3 Topology with Component Count Reduction 10.3.1. Model 10.3.2. PWM Strategy 10.3.3. Dc-link Voltage Requirement 10.3.4. Half-bridge Converter 10.4 Topologies with increased number of switches (Converters in Parallel) 10.4.1. Model 10.4.2. PWM Strategy 10.4.3. Control Strategy 10.5 Topologies with increased number of switches (Converters in Series) 10.6 Summary 10.7 References 11. Chapter 11. Three-phase to Three-phase and Other Backto- Back Converters 11.1 Introduction 11.2 Full-Bridge Converter 11.2.1. Model 11.2.2. PWM Strategy 11.2.3. Control Approach 11.3 Topology with Component Count Reduction 11.3.1. Model 11.3.2. PWM Strategy 11.3.3. Dc-link Voltage Requirement 11.3.4. Half-bridge Converter 11.4 Topologies with increased number of switches (Converters in Parallel) 11.4.1. Model 11.4.2. PWM 11.4.3. Control Strategy 11.5 Topologies with increased number of switches (Converters in Series) 11.6 Other Back-to-back Converters 11.7 Summary 11.8 References .
Keywords: PWM power converters; DC-to-DC converters; Power electronics